Kinerja Pemungutan Suara dalam Pemilihan Kepala Daerah pada Masa Pandemi Covid – 19 di Kabupaten Maluku Barat Daya - Oktovian Samangun; Zainal Abidin Rengifurwarin; Petronela Sahetapy (Universitas Indo Global Mandiri, 2023)
This research aims to analyze and explain the performance of election during the covid-19 pandemic and the effectiveness of the supervisory role by the Election Supervisory Board (Bawaslu) in Southwest Maluku Regency. This research seeks to find out: How was the performance of voting activities during the Covid-1 pandemic in the regional head election of Southwest Maluku Regency? and How effective was the role of the Election Supervisory Board in supervision the during the Covid-19 pandemic in Southwest Maluku Regency? This research is qualitative in nature with the number of informants as many as 8 people. Data were collected and analyzed through qualitative analysis techniques. The findings of this research suggest that the performance of voting activities in the regional head election during the Covid-19 pandemic was in good condition. Meanwhile, the effectiveness of the role of monitoring the performance of these voting activities by the Election Supervisory Board of Southwest Maluku Regency was in an optimal position. The implication of the results of this research is that to improve the performance of voting activities during the COVID-19 pandemic, then the effectiveness of the supervision by the Election Supervisory Board in a Regency must be optimized.